OCT parameters of the optic nerve head and the retina as surrogate markers of brain volume in a normal population, a pilot study - Mejia-Vergara, Alvaro J.; Karanjia, Rustum; Sadun, Alfredo A. (Journal of the neurological sciences, 2021)
The relationship between optical coherence tomography (OCT) measurements of the retinal structures has been described for various neurological diseases including Multiple Sclerosis (MS), Alzheimer's disease (AD) and Parkinson's disease (PD). Brain volume changes, both globally and by area, are associated with some of these same diseases, yet the correlation of OCT and disease is not fully elucidated. Our study looked at normal subjects, at the correlation of OCT measurements and brain volumes, both globally and for specific regions including the pericalcarine grey matter, entorhinal grey matter, and cerebellar volume using a retrospective, cross-sectional cohort study design. Thickness of the retinal nerve fiber layer (RNFL) as measured by OCT, correlated with volume of the pericalcarine grey matter, when adjusted for age and gender. Similarly, thickness of the ganglion cell layer-inner plexiform layer complex may be associated with both entorhinal grey matter volumes and total cerebellar volumes, although our pilot study did not reach statistical significance. This suggests that both eye and brain volumes follow a similar trajectory and understanding the inter-relationship of these structures will aid in the analysis of changes seen in disease. Further studies are needed to longitudinally demonstrate these relationships. •RNFL measured by OCT is correlated with MRI brain volumetric analysis of the pericalcarine grey matter in normal subjects.•Intracranial volumes and cerebellar volumes vary with age consistent with previously reported results.•OCT in-vivo measures of the retina demonstrates retinal changes parallel changes in different regions of the brain.